2018
DOI: 10.31234/osf.io/kx6y8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Centrality in a Cross-Sectional Network Suggest Intervention Targets for Social Anxiety Disorder?

Abstract: Objective: Network analysis allows us to identify the most interconnected (i.e., central) symptoms, and multiple authors have suggested that these symptoms might be important treatment targets. This is because change in central symptoms (relative to others) should have greater impact on change in all other symptoms. It has been argued that networks derived from cross-sectional data may help identify such important symptoms. We tested this hypothesis in social anxiety disorder. Method: We first estimated a stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 37 publications
2
58
0
Order By: Relevance
“…Identifying bridge nodes may enhance our understanding of comorbidity processes (c.f. Rodebaugh et al, ). Moreover, simulations that model the spread of one psychiatric disorder to others suggest that when treating comorbidities, bridge nodes may represent the most influential intervention targets (Jones et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying bridge nodes may enhance our understanding of comorbidity processes (c.f. Rodebaugh et al, ). Moreover, simulations that model the spread of one psychiatric disorder to others suggest that when treating comorbidities, bridge nodes may represent the most influential intervention targets (Jones et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, debate exists about whether central nodes identified in cross‐sectional networks are meaningful intervention targets. Emerging evidence supports that central nodes in cross‐sectional networks can predict treatment outcomes (Olatunji, Levinson, & Calebs, ; Rodebaugh et al, ), but prediction may depend on whether the same measures are used to estimate the network and assess outcomes (Rodebaugh et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The informative value of centrality indices in psychological networks is currently debated. Some studies have shown that central elements of psychopathology networks have high clinical relevance (Boschloo, van Borkulo, Borsboom, & Schoevers, ; Christensen, Kenett, Aste, Silvia, & Kwapil, ; Rodebaugh et al, ). However, centrality indices have been originally developed for social networks and might not be adequate to capture the type of relationships encoded by psychological networks (Bringmann & Eronen, ).…”
Section: Network Analysesmentioning
confidence: 99%
“…However, a study on social anxiety disorder (Rodebaugh et al 2018) found that although degree centrality (not closeness or betweenness centrality) seemed to have some utility in predicting change processes and social anxiety severity, it was simply the number of times that patients endorsed (i.e., reported) a symptom that had the most predictive power in indicating which items were the most important ones. The authors conclude that clinicians could use highly central symptoms of cross-sectional networks, but simply treating the most commonly reported symptoms would probably work better (Rodebaugh et al, 2018). Furthermore, there remains a lack of studies on the predictive value of centrality indices in temporal networks.…”
Section: Introductionmentioning
confidence: 99%